Proses Mediasi Perceraian di Kalangan PNS di Kota Padang Sidempuan - Setiadi, Afifah Farha; Mukhsin, Abdul (Universitas Medan Area, 2025)
Marriage is a physical and spiritual bond between a man and a woman, which is expected to create a sense of sakinah, mawaddah, and warahmah. To achieve this in marriage requires an attitude of mutual understanding and comprehension, especially those related to the rights and obligations of a husband and wife. In married life, one thing that cannot be avoided is conflict. One of the factors causing conflict is that the rights that must be obtained are not fulfilled or the obligations of one party are not carried out. Other reasons can result in a dispute between the two parties, so mediation is needed to resolve the problems that occur. The dispute may result in divorce. In the divorce process, mediation will be carried out with the aim of considering whether the household can still be maintained. This study aims to describe and analyze the capacity of the mediator in the mediation process that occurs among Civil Servants. This study uses a qualitative descriptive method. This study uses primary data and secondary data. Based on the results of data analysis, it was found that the average divorce rate in Civil Servants (PNS) in Padangsidimpuan City Agencies was 4.4 people/year or 0.79%. The effectiveness of mediators in resolving problems in the divorce process is considered less effective.